Anomaly Detection in Network Access-Using LSTM and Encoder-Enhanced Generative Adversarial Networks - Hu, Jian; He, Yingjun; Xu, Wenqian; Jiang, Yixin; Liang, Zhihong; Yang, Yiwei (Informatica, 2025)
Along with the continuous development of information technology, the database has become an important module for enterprises and individuals to apply computers, and some important data are stored in the database, which also leads to the database becoming the target of malicious intruders. The abnormal access behavior detection algorithm for data can quickly identify abnormal access situations, timely intervention and processing to ensure data security. Based on this, this paper proposes an abnormal defense behavior detection algorithm based on generative adversarial network, the new algorithm has the applicability as well as two derivative models of generative adversarial network for network abnormal access detection with high efficiency. In this paper, we experiment the classification accuracy of network anomaly detection algorithm, i.e., F1, by using three models, namely, the original Generative Adversarial Network (GAN), Generative Adversarial Network using Long and Short-Term Memory Network (GAN+LSTM), and Generative Adversarial Network with the addition of an encoder (GAN+Encoder), and the result of this paper shows that the GAN+Encoder model is the most effective. And based on these three models of the generator and discriminator loss trends are compared, as well as through the iteration of 50 times of training results show that the GAN + Encoder model is relatively simple, and the training time is shorter and more efficient.